The Effect of Sodium Tripolyphosphate and Guar Gum on Physical Characteristics of Analog Rice from Gaplek Flour - Puspitasari, Dyah Ayu; Pudjianto, Karjawan; Darussalam, Abdullah; Wicaksana, Galuh Hendhitya; Hastuti, Heru Pitria (agriTECH, 2024)
Gaplek flour is a processed product of cassava preservation abundant during the harvest season in Lampung Province. The high carbohydrate content in cassava facilitates the processing of gaplek flour into carbohydraterich food source, such as analog rice. Therefore, this study aimed to investigate the effect of adding STPP and guar gum on the formulation of analog rice made from 70% gaplek flour and 30% corn flour. Analog rice was produced using the extrusion method with a twin-screw extruder. The results showed that the addition of STPP did not affect water absorption characteristics. The solubility of rice in deep water also decreased with increasing amounts of STPP and guar gum. Meanwhile, guar gum significantly increased water absorption and reduced the solubility of rice in water. The degree of gelatinization decreased with the addition of both materials. The addition of 0.3-0.5% STPP and 0.5-2% guar gum had no significant effect on hardness, stickiness, elasticity, and cohesiveness of analog rice prepared using a cooker.